Depressive and anxiety symptoms in postpartum women after recovery from COVID-19: a questionnaire-based observational study - Hsieh, Chia-Jung; Su, Hsiu-Wei; Lee, Chen-Yu; Lin, Chih-Chien; Chen, Wei-Chih (Frontiers in Public Health, 2024)
IntroductionPrevious studies on the association between recovery from Coronavirus Disease 2019 (COVID-19) infection and postpartum depressive and anxiety symptoms had conflicting results. This study aimed to investigate the psychological burdens among postpartum women who had experienced COVID-19 infection during their pregnancies and those who had not.MethodsThis cross-sectional study was conducted at Taichung Veterans General Hospital in Taiwan from April 2022 to January 2023. A total of 113 postpartum women completed self-reported questionnaires, including the Edinburgh Postnatal Depression Scale (EPDS) and General Anxiety Disorder-7 (GAD-7), in the postpartum clinics or wards.ResultsFifty-four individuals (47%) who experienced COVID-19 infection during their pregnancies and 59 uninfected women completed the questionnaires. The mean EPDS scores were 5.00 ± 4.26 vs. 6.46 ± 4.50 (p = 0.09) and the mean GAD-7 scores were 3.17 ± 2.88 vs. 3.69 ± 2.73 (p = 0.21). Multivariate linear regression analyses revealed that factors associated with lower EPDS scores included experiencing COVID-19 infection during pregnancy, delivery by expected mode, and neonates not requiring admission to the Intensive Care Nursery (ICN) or Neonatal Intensive Care Unit (NICU). Delivery by expected mode was the only variable associated with a lower GAD-7 score in the multivariate model.ConclusionOur study demonstrated that COVID-19 infection during pregnancy was associated with fewer postpartum depressive symptoms based on linear regression analysis, with no significant difference in postpartum anxiety symptoms.